Advanced Practical Applications of Computational Biology & Bioinformatics: PACBB15 - Rocha, Miguel (2018)
[Excerpt] The success of Bioinformatics in recent years has been prompted by research in Molecular Biology and Molecular Medicine in several initiatives. These initiatives gave rise to an exponential increase in the volume and diversification of data, including next generation sequencing data and their annotations, high-throughput experimental (omics) data, biomedical literature, among many others. Systems Biology is a related research area that has been replacing the reductionist” view that dominated Biology research in the last decades, requiring the coordinated efforts of biological researchers with those related to data analysis, mathematical modeling, computer simulation and optimization. [...]